Proceedings of the International Symposium on Sketch-Based Interfaces and Modeling 2013
DOI: 10.1145/2487381.2487385
|View full text |Cite
|
Sign up to set email alerts
|

Automatic single-view character model reconstruction

Abstract: Figure 1: This paper presents a method for automatically constructing 3D meshes from a single piece of concept artwork. This figure shows how a typical 2D concept image (a) is separated from the background (b) and how a bent skeleton (c) is generated and used to create polygonal shells (d). The profile view (e) shows clearly how the shells create a 3D representation of the input image. The final model (f -h) is mapped with textures based on the initial concept artwork and contains bone and vertex weighting inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…As pointed out by Bessmeltsev et al [2015], modeling a posed character given a single contour sketch is inherently ambiguous, as the contours alone allow multiple perceptually plausible interpretations. To generate the user-desired models, existing methods either rely on incremental contour drawing order [Cherlin et al 2005], employ primitive-based annotation [Cherlin et al 2005;Gingold et al 2009;Shtof et al 2013], require users to provide a matching posed 3D skeleton , or enforce a range of strong simplifying assumptions [Cordier et al 2011;Buchanan et al 2013;Karpenko and Hughes 2006] -for instance, Cordier et al [2011] only handle mirror-symmetric poses, while other methods assume that the 3D generators of the drawn contours are planar and near-parallel to the view plane [Buchanan et al 2013;Karpenko and Hughes 2006;Bai et al 2016], an assumption that does not hold for most character poses . Our work addresses generic gesture drawings with no such limitations (Figure 1), solving an essentially inverse problem to that of : instead of computing a character geometry given a sketch and a 3D pose, we compute a character pose given a gesture drawing and a character model.…”
Section: Sketch Based Modelingmentioning
confidence: 99%
“…As pointed out by Bessmeltsev et al [2015], modeling a posed character given a single contour sketch is inherently ambiguous, as the contours alone allow multiple perceptually plausible interpretations. To generate the user-desired models, existing methods either rely on incremental contour drawing order [Cherlin et al 2005], employ primitive-based annotation [Cherlin et al 2005;Gingold et al 2009;Shtof et al 2013], require users to provide a matching posed 3D skeleton , or enforce a range of strong simplifying assumptions [Cordier et al 2011;Buchanan et al 2013;Karpenko and Hughes 2006] -for instance, Cordier et al [2011] only handle mirror-symmetric poses, while other methods assume that the 3D generators of the drawn contours are planar and near-parallel to the view plane [Buchanan et al 2013;Karpenko and Hughes 2006;Bai et al 2016], an assumption that does not hold for most character poses . Our work addresses generic gesture drawings with no such limitations (Figure 1), solving an essentially inverse problem to that of : instead of computing a character geometry given a sketch and a 3D pose, we compute a character pose given a gesture drawing and a character model.…”
Section: Sketch Based Modelingmentioning
confidence: 99%
“…The system then wraps the spine with the polygonal mesh and then uses constraint Delaunay triangulation of the polygon. Pruning of insignificant branches is performed using [Prasad 1997]. The algorithm progresses through several refinement steps to obtain a smooth and symmetric 3D surface.…”
Section: Single View Systemsmentioning
confidence: 99%
“…Automatic single-view character model reconstruction: Buchanan et al [Buchanan et al 2013] have demonstrated a system which generates lowpolygon models directly from input character sketches without any interactivity by the artist. Their algorithm first computes a skeleton from the image and then draws cross section curves along the skeleton using a novel proposed heuristic.…”
Section: Structured Annotations For 2d-to-3d Modelingmentioning
confidence: 99%
See 2 more Smart Citations